(untitled) (Nigerian Journal of Physiological Sciences, 2025)
This study described the peculiarity of the clinical phenotypes and the pattern of reproductive hormones among women with PCOS in Nigerian populace. A total of 90 consented volunteers consisting of 45 PCOS and 45 controls were recruited. The diagnosis of PCOS was established using the International PCOS guidelines 2018. Demographic, anthropometric, and clinicopathological data were obtained from each participant. Hormonal assay was done using the electrochemiluminescence (ECL) technology (Roche Diagnostics, Switzerland). Statistical analysis was done using the Statistical Package for the Social Sciences (SPSS) version 25. Polycystic ovaries (PCO) are the most popular feature of PCOS, observed in more than 90% of PCOS subjects followed by oligomenorrhea (68 %), while hirsutism and acne were found in about 50% of the cases. The study shows 62 % of PCOS subjects had phenotype D, 52 % Phenotype C, 40 % Phenotype B, while 38 % had Phenotype A. Increased levels of Anti-Mullerian hormone (AMH), Testosterone, Prolactin, Luteinizing hormone (LH) and LH: FSH were observed in PCOS with median (95% Confidence interval) of 4.98(3.4-7.1), 32.5(19.75-53.0), 401.6(230.9-623.0), 9.23(5.4-16.6) and 2.03(1.48-3.58), respectively compared to control [1.43(0.8-2.4), 19.0(12.3-29.5), 252.2(196.3-337.0), 6.36(4.0-12.6) and 1.47(0.7-2.4), respectively] (p<0.05). The serum levels of follicle-stimulating hormone (FSH), estradiol, and sex hormone binding globulin (SHBG) were lower in PCOS with values of 5.21(3.6-5.9), 70.45(50.5-145.9) and 44.84(27.3-75.7), respectively compared to controls [6.0(4.4-7.9), 104.0(64.6-216.6) and 74.05(54.0-96.8), respectively] (P<0.05). FSH, LH:FSH, AMH, testosterone, estradiol, SHBG, and prolactin show significant odd ratio with risk analysis in PCOS (p<0.05). There existed a negative correlation between the hormones (Estradiol and AMH) and the PCOS phenotypes (estimated Spearman’s rho were -.310 and -.348, respectively) (p<0.05). Phenotype D and C characterized by ovulatory dysfunction, polycystic ovary morphology and hyperandrogenism are the two predominant phenotypes of PCOS in our study population. This is accompanied by marked changes in hormonal pattern among PCOS subjects, particularly steroids and follicular hormones. Modulating this phenotype-hormonal interplay may support or improve PCOS management in the study population